Syntheses, Characterization and biological Activity of a new ligand [N-(5-sulfanyl-1,3,4-thiadiazol-2-yl)acetamide with some transition metal complexes - weam .A. * Salman (University of Thi-Qar Journal of Science, 2019)
A-new series of transition metal (Cr(III),Fe(III), Co(II) , Ni(II)and Cu(II) ) complexes of ligand [N-(5-sulfonyl-1,3,4,thiadiazol-2-yl)acetamide were synthesized. All the synthesized complexes were characterized by analytical techniques, magnetic susceptibility measurements, elemental analyses, conductance, IR , 1HNMR and mass spectra. The electrolytic behavior were confirmed from their conductance data . It may be concluded that the ligand coordinate through Nitrogen and sulfur atoms as shown in figure (6). for all complexes. The ligand acts as a didentate ligand coordinating through the sulfur[S6] and the nitrogen atom of shiff base [N5]. This view is further supported by the appearance of a band corresponding to the metal–nitrogen stretching vibration at( 547–563) cm–1 in the complexes. From results it was suggested tetrahedral geometry for Ni(II) and Cu(II) complexes, while Cr(III),Fe(III) and Co (III)complexes were assigned octahedral geometrics. All complexes and their parent organic moiety have been screened for antibacterial by using spread method and measurement inhibition zone by using (DMSO). this study showed positivity results, by comparison of inhibition zone with E-coli and staph aurens.